Perception, attitudes and factors influencing and limiting participation in Continuous Professional Development (CPD) activities among physiotherapists in Kuala Lumpur and Selangor / Fatin Athirah Rahman, Amira Dayana Amirulzaini, Fatim Tahirah Mirza - Rahman, Fatin Athirah; Amirulzaini, Amira Dayana; Mirza, Fatim Tahirah (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Introduction: The developing fields of science, technology, and healthcare have made it essential for healthcare workers especially physiotherapist to continuously learn throughout their life. Objectives: To determine the perception and attitude, factors influencing and limiting and the association between demographic characteristics with participation in CPD activities among physiotherapist in Kuala Lumpur and Selangor. Methods: A cross-sectional study was conducted on 143 physiotherapists in Kuala Lumpur and Selangor. Self-administered questionnaire was distributed through google form. Results: Physiotherapists had positive attitude towards participation in CPD activities. Majority (92%) of the study respondents agreed on lifelong learning as part of what it means to be a professional and 95% of them feels that keeping up to date with knowledge or skills was the most beneficial aspect of CPD. The most (99%) factor influencing participation in CPD activities was 'to improve professional knowledge' while the most (83%) factor limiting participation in CPD activities was time constraints. Significant relationships were found between age (p = 0.031), working area (p=0.001) and working experience (p = 0.008) with participation in CPD. Conclusion: Physiotherapists in Kuala Lumpur and Selangor demonstrated a positive perception and attitude towards participation in CPD activities. They admitted that continuing education is a must for their professional development.